Analytical Methods Used for the Detection and Quantification of Benzodiazepines - Zidane Qriouet; Zineb Qmichou; Nadia Bouchoutrouch; Hassan Mahi; Yahia Cherrah; Hassan Sefrioui (Journal of Analytical Methods in Chemistry)
The prescription of psychotropic drugs, especially benzodiazepines (BZDs), occupies a preponderant place in the management of mental illnesses. Indeed, the BZDs have been used in different therapeutic areas including insomnia, anxiety, seizure disorders, or general anesthesia. Unfortunately, these drugs are present in the illegal street market, leading to a lot of drug abuse amongst some addicted users, road insecurity, and suicide. Hence, it has become essential to analyze the BZDs drugs in human biological specimens for drug abuse in forensic sciences. The present review provides a summary of sample preparation techniques (solid-phase extraction and Liquid-liquid phase extraction) and the methods for the detection and quantification of BZDs molecules in the commonly used biological specimens over the ten last years which may potentially lead to better and accurate evaluation of the physiological state of a given person. The commonly used methods for the detection and quantification of BZDs include nuclear magnetic resonance (NMR), chromatography (GC-MS, HPLC, and TLC), immunoassay (ELISA, RIA, LFA, CEDEA, FPIA, and KIMS), and electroanalytical methods (voltammetry and potentiometry).